Monopoly Game as A Science Learning Media for Junior High School; A Validity Analysis - Yusuf, Muhammad; Susanti, Try; Sembiring, Dian Arisandy Eka Putra (Universitas Syiah Kuala, 2023)
Learning media is important as a means of delivering information to students. Media is not only interesting in terms of content, but also able to adjust to the characteristics of students. This study aims to reveal the validity of science learning media in the form of a monopoly game. This research uses descriptive analysis method. This research involved experts to assess the learning media being developed, namely content experts, media experts, and language experts. The instrument used in this research is a validation sheet. Data were collected through expert assessment questionnaires (as validators). Data analysis in the form of numerical values is done quantitatively, while comments or suggestions are done qualitatively. The results showed that the media was valid. Further tests were carried out, to assess the effectiveness of the media, so as to reveal more feasibility of the media.